Elucidating the influence of structure and Ag+ -Na+ ion-exchange on crack-resistance and ionic conductivity of Na3Al1.8Si1.65 P-1.8 O-12 glass electrolyte - Keshri, Shweta R.; Mandal, Indrajeet; Ganisetti, Sudheer; Kasimuthumaniyan, S.; Kumar, Rajesh; Gaddam, Anuraag; Shelke, Ankita; Ajithkumar, Thalasseril G.; Gosvami, Nitya Nand; Krishnan, N. M. Anoop; Allu, Amarnath R. (Acta Materialia, 2022)
Glasses are emerging as promising and efficient solid electrolytes for all-solid-state sodium-ion batteries. However, they still suffer from poor ionic conductivity and crack-resistance, which need to be improved for better battery performance, reliability, and service life. The current study shows a significant enhancement in crack resistance (from 11.3 N to 32.9 N) for Na3Al (1.8) Si-1.65 P1.8O12 glass (Ag-0 glass) upon Na+ -Ag+ ion-exchange (IE) due to compressive stresses generated in the glass surface while the ionic conductivity values (similar to 10(-5) S/cm at 473 K) were retained. In this study, magic angle spinning-nuclear magnetic resonance (MAS-NMR), molecular dynamics (MD) simulations, Vickers micro hardness, and impedance spectroscopic techniques were used to evaluate the intermediate-range structure, atomic structure, crack resistance and conductivity of the glass. MAS-NMR and MD simulations confirm the presence of Si-OAl-O-P groups in the glass, thus enabling formation of Na percolated channel regions. AC-conductivity analysis for Ag-0 and ion-exchanged Ag-0 glass suggests that the mobility of Na+ ion increases with increasing temperature. It is observed that the measured mean square displacement (root < R-2(t(p))>) for sodium cations using AC-conductivity isotherms is nearly constant up to 448 K and then increases with increasing temperature up to 523 K. From the impedance spectra for ion-exchanged Ag-0 glass, it is identified that the increase in root < R-2 (t(nu))> and thereby, the mobility of sodium-ions for Ag-0 glass is due to the structural variations in the Ag-0 glass with increasing the temperature. Overall, the mechanisms presented in this article helps in formulating better glass based electrolyte materials for room temperature or high temperature sodium-ion batteries. (C) 2022 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: amorphous; Ion-exchange; Ionic-conductivity; MD simulations; Mechanical property

Extraction, characterization, and life cycle assessment of nanosilica from millet husk: sustainable alternative with low environmental impact - Dominic, C. D. Midhun; Rosa, Derval dos Santos; Barbosa, Rennan Felix da Silva; Anagha, O. V.; Neenu, K. V.; Begum, P. M. Sabura; Kumar, V. Aswathy; Parameswaranpillai, Jyotishkumar; Siriwong, Chomsri; Ajithkumar, T. G.; Shelke, Ankita; Pasc, Andreea (Journal of Cleaner Production, 2024)
Eco-friendly approaches for silica production are highly researched to respond increasing industrial demand for bio-nanofillers. Herein, nanosilica of 10-20 nm with mesoporosity was obtained through a mild oxalic acid pre-treatment of millet husk, followed by calcination at 700 degrees C for 2 h. Compared with commercial precipitated silica (CS) and millet husk ash (MHA) directly obtained by calcination of the husk, the pre-treated silica (MHS) had higher purity, revealed using EDX spectroscopy. Moreover, FTIR and Si-29 NMR showed a higher condensation degree in MHS with 73% of Q4 siloxane bonds vs 4% in MHA. The release of the metal and organic impurities from the husk also allows to reduce the crystallinity of MHS, and to increase the specific surface area from 82 m(2)/g in MHA to 238 m(2)/g in MHS. The type II N-2 adsorption-desorption isotherms of MHA and MHS indicate aggregates of non-porous silica particles. MHS also demonstrated remarkable thermal resilience. According to the LCA analysis, MHS has a 40% lower impact on global warming, a 38% lower impact on human carcinogenic toxicity, and a 38% lower impact on terrestrial acidification compared to rice husk nanosilica. This research thus addresses sustainability challenges by repurposing millet husks, which are readily available due to continuous millet cultivation, particularly in India. By reducing the ecological impact of husk disposal through burning, this study offers an economically viable technology for high-purity silica production, aligning with global efforts to combat climate change and promote sustainable practices.
Keywords: Life cycle assessment; Millet husk; Nanosilica; Oxalic acid

Effect of sulfonation density on acid strength in ion exchange resins: Insights from solid-state NMR and density functional theory - Tumulu, Goutam Narayan; Datar, Sarvesh; Shelke, Ankita; Swain, Gitanjali; Ajithkumar, T. G.; Thirumalaiswamy, Raja; Mohan, Ojus; Mahajani, Sanjay M. (Molecular Catalysis, 2026)
Ion-exchange (IE) resins are widely used as solid acid catalysts; however, their surface acidity remains poorly characterized because their limited thermal stability precludes conventional NH3-based acidity measurements. Moreover, acid-site accessibility in IE resins is strongly governed by solvent- or reactant-induced swelling. Here, we investigate the surface acidity of commercial Amberlyst and Indion IE resins using & sup3;& sup1;P MAS NMR (Magic Angle Spinning Nuclear Magnetic Resonance), employing TMPO as a molecular probe dispersed on the resin with moderately swelling dichloromethane, thereby capturing the swollen-state acidity relevant for predicting catalytic activity. The deconvolution of the P-31 MAS NMR spectra reveals three distinct acid-strength zones arising from inhomogeneous sulfonation of the polymer matrix. The overall acidity, quantified by the area-weighted average P-31 chemical shift (delta), increases monotonically with sulfonation density. Notably, only resins containing acid sites stronger than similar to 80 ppm exhibited measurable catalytic activity in alpha-pinene isomerization, establishing a direct correlation between acidity and activity. Density functional theory (DFT) calculations on representative resin models, supported by electron-density analyses, attribute the enhancement of acid strength at higher sulfonation densities to cooperative hydrogen-bonding networks among neighboring sulfonic acid groups. Together, these findings establish P-31 MAS NMR-derived surface acidity as a catalytically relevant descriptor for the rational selection of IE resins in liquid phase acid-catalyzed chemistries.
Keywords: Acid strength; Density functional theory; heterogeneous catalysis; Ion-exchange resins; Solid acids; Solid-state NMR